FUNGSI DAN PERAN AGAMA DALAM PERUBAHAN SOSIAL INDIVIDU, MASYARAKAT - Deni Irawan (Borneo : Journal of Islamic Studies, 2022)
Religion on the one hand is sometimes likened to "two sides of a coin" that cannot be separated. It becomes an inseparable part. The role of religion in an individual's life functions as a value system that contains certain norms. Religion is influential as a motivator to encourage individuals to carry out activities, because actions taken in the context of religious beliefs are seen as elements of purity and obedience. Religion in personal life also functions as 1). Valuable resource for maintaining morale 2). 3) As a means of overcoming frustration and as a means of satisfying curiosity. While the functions of religion in social life include 1) Functional education, 2). Savior, 3) As redemption, 4). As social control, 5). As a driver of solidarity. 6). Transformational function, 7). Creative function, 8). Sublimation function. This article was compiled using descriptive qualitative methods to reveal the function and role of religion in social change of individuals and communities.